PENGEMBANGAN LEMBAR KEGIATAN SISWA BERBASIS DISCOVERY LEARNING UNTUK MENINGKATKAN BERPIKIR KREATIF - Presthia Wulandari; Nurhayati Nurhayati; Murni Sianturi (Musamus University, 2019)
Abstract: This study aims to develop discovery learning student worksheets in class VIII of SMP Negeri 4 Kurik and to improve the ability to think creatively in mathematics learning for material in Two Variable Linear Equation Systems (SPLDV). The instrument of data collection in this study is a matter of pre-test and post-test, questionnaire, observation and documentation. This type of research uses development research, research design using the model of Analysis, Design, Development, Implementation, Evaluation (ADDIE), the subject of research is VIIIA grade students of SMP 4 Kurik. The object of the research is student worksheets with the subject matter of two-variable linear equation systems. Development research methods, including research design, research sites, subjects, data sources, data collection techniques, research instruments and data analysis techniques using tabulation data to determine the increase after and before using student worksheets. The results of the study and conclusions obtained the level of mathematical creative thinking of class VIIIA students of SMP N 4 Kurik after being tested on this student worksheet of 92.19% with a level of creative thinking in the aspect of fluency of 90.63%, aspects of flexibility 95.83%, aspects of authenticity of 92 , 71%, and detail aspects 89.58%. This shows that this student worksheet is effectively used in teaching and learning activities. Keywords: Student Worksheets, Discovery Learning, Creative Thinking.